2019
DOI: 10.14569/ijacsa.2019.0100310
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Average Queue Length in Active Queue Management Method

Abstract: This paper proposes the Stabilized (DGRED) method for congestion detection at the router buffer. This method aims to stabilize the average queue length between allocated minthre_shold and doublemaxthre_shold positions to increase the network performance. The SDGRED method is simulated and compared with Gentle Random Early Detection (GRED) and Dynamic GRED active queue management methods. This comparison is built on different important measures, such as dropping probability, throughput, average delay, packet lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The DGRED depends on the three-state markov modulated bernoulli arrival process (MMBP-3) to support three types of the traffic flow by performing correlation among these network traffics. An extension of DGRED is stabilized dynamic GRED "SDGRED" [21], [22] to provide dynamically stabilizing the avg between min th and max th . This dynamic algorithm uses dynamic increase or decrease of max th and doublemax th value by stabilizing the avg value around min th to adjust the calculation of dropping probability.…”
Section: Figure 3 Red Algorithmmentioning
confidence: 99%
“…The DGRED depends on the three-state markov modulated bernoulli arrival process (MMBP-3) to support three types of the traffic flow by performing correlation among these network traffics. An extension of DGRED is stabilized dynamic GRED "SDGRED" [21], [22] to provide dynamically stabilizing the avg between min th and max th . This dynamic algorithm uses dynamic increase or decrease of max th and doublemax th value by stabilizing the avg value around min th to adjust the calculation of dropping probability.…”
Section: Figure 3 Red Algorithmmentioning
confidence: 99%
“…Table 1 compares the existing AQM algorithms and highlights the gaps that will be covered in this paper. Unlike in DGRED, all thresholds in the SDGRED algorithm change following the status of aql at the router buffer [16]. Moreover, SDGRED eliminates Taql to decrease the parameterization in the router buffer.…”
Section: Related Workmentioning
confidence: 99%
“…To face such a challenge, many active queue management (AQM) algorithms were developed and improved to detect congestion at an early stage and improve network performance. Several examples include the enhanced adaptive gentle random early detection (GRED) [15], stabilized dynamic GRED (SDGRED) [16], Markov-modulated queuing systems [17], FL Intelligent Traffic Management [18], fuzzy logic approach for congestion control [19], and dynamic GRED (DGRED) [20], Markov-modulated [17], FLACC [19], and dynamic stochastic early discovery [20]. These algorithms, although they have great influence in easing the congestion, suffer from some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm aimed at stabilizing ave at a computed specified value between minTh and maxTh while dynamically adjusting the queue thresholds: maxTh and two times maxTh in order to provide an improved performance in terms of packet loss rate. Baklizi et al [29] suggested the stabilized DGRED (SDGRED) algorithm, a modified version of DGRED whereby the maxTh and two times maxTh queue thresholds were dynamically adjusted and aimed at stabilizing ave at a computed specified value between minTh and two times maxTh queue thresholds in order to obtain a reduced packet loss rate and queuing delay. Weight queue dynamic AQM (WQDAQM) algorithm [30] is an improvement over SDGRED algorithm.…”
Section: Introductionmentioning
confidence: 99%